2017
DOI: 10.1016/j.surfcoat.2017.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and wear resistance of Ti6Al4V surfaces processed by pulsed laser

Abstract: When pulsed laser beams deposit spatially and temporally localized power on the metallic surfaces, microstructure and mechanical properties could change significantly. During and after each pulse, the exposed surface experiences a cycle of thermal processes involving extremely high heating and cooling rates, which consequently cause significant microstructure evolution. Changes in mechanical strength follow such microstructural changes. In this work, the influence of pulsed laser processing (PLP) on microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…A wide range of techniques of TMC fabrication is used nowadays, they can be classified into five categories liquid-phase processes, (2) solid-liquid processes, (3) two-phase (solid-liquid) processes, (4) deposition techniques and (5) in situ processes [29]. Although it is possible to find mentions of TMC deposition by laser-assisted direct deposition [36], [37], [38], [39], [40], it is almost impossible to find a mention in the literature of the possibility of producing TMC by PTA hardfacing method, only Ti Gr. 1 was tested [41].…”
Section: Figure 1feedstock Powder Of Ti6al4v and B4cmentioning
confidence: 99%
“…A wide range of techniques of TMC fabrication is used nowadays, they can be classified into five categories liquid-phase processes, (2) solid-liquid processes, (3) two-phase (solid-liquid) processes, (4) deposition techniques and (5) in situ processes [29]. Although it is possible to find mentions of TMC deposition by laser-assisted direct deposition [36], [37], [38], [39], [40], it is almost impossible to find a mention in the literature of the possibility of producing TMC by PTA hardfacing method, only Ti Gr. 1 was tested [41].…”
Section: Figure 1feedstock Powder Of Ti6al4v and B4cmentioning
confidence: 99%
“…Laser surface modifications can enhance wear resistance and friction properties of the implant [17]. Chen et al [17] demonstrated that surfaces treated with high laser power showed higher hardness and wear resistance than the untreated and surfaces treated by low laser power.…”
Section: Laser Effect On the Implant Tribo-mechanical Propertiesmentioning
confidence: 99%
“…Low hardness values and poor tribological characteristics of metallic implant materials can be improved by laser powder deposition [18]. Comparing the Ti-6Al-4V substrate characteristics with the characteristics of the Ti-Al intermetallic coating formed on the Ti-6Al-4V alloy surface ( Figure 6), Liu et al [20] noticed that intermetallic coating displays lower friction coefficients due to the higher hardness values since the biometallics hardness and wear resistance are greatly influenced by each other [17][18][19][20].…”
Section: Laser Effect On the Implant Tribo-mechanical Propertiesmentioning
confidence: 99%
“…In the process of friction and wear, textured surface can effectively reduce the wear and tear, and improve the service life (Rosenkranz et al, 2019). At present, the methods of surface texture processing mainly include laser processing, mechanical processing, chemical etching and so on, among these methods, laser processing is widely used because of its high efficiency, strong penetrating power, small impact on the environment, and can improve the hardness of metal surface (Gualtieri et al, 2009;Chen et al, 2017). Etsion and Burstein (1996) and Etsion (2004) have laid a foundation for the pioneering work of improving tribological properties of laser surface texturing (LST).…”
Section: Introductionmentioning
confidence: 99%